2013
DOI: 10.1099/ijs.0.044065-0
|View full text |Cite
|
Sign up to set email alerts
|

Sunxiuqinia faeciviva sp. nov., a facultatively anaerobic organoheterotroph of the Bacteroidetes isolated from deep subseafloor sediment

Abstract: A facultatively anaerobic organoheterotroph, designated JAM-BA0302 T , was isolated from a deep subseafloor sediment at a depth of 247.1 m below the seafloor off the Shimokita Peninsula of Japan in the north-western Pacific Ocean (Site C9001 , water depth 1180 m). Cells of strain JAM-BA0302 T showed gliding motility and were thin, long rods with peritrichous fimbriae-like structures. Growth occurred at 4-37 6C (optimum 30 6C; doubling time 8 h), at pH 5.4-8.3 (optimum pH 7.5) and with 5-60 g NaCl l "1 (optimum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 50 publications
0
29
1
Order By: Relevance
“…T (Qu et al, 2011;Takai et al, 2013). Symbols: GL, glycolipid; PE, phosphatidylethanolamine; UL, unidentified lipid; UAL, unidentified aminolipid; UPL, unidentified phospholipid; +, positive; , negative; ND, no data available.…”
Section: Description Of Sunxiuqinia Rutila Sp Novmentioning
confidence: 99%
See 1 more Smart Citation
“…T (Qu et al, 2011;Takai et al, 2013). Symbols: GL, glycolipid; PE, phosphatidylethanolamine; UL, unidentified lipid; UAL, unidentified aminolipid; UPL, unidentified phospholipid; +, positive; , negative; ND, no data available.…”
Section: Description Of Sunxiuqinia Rutila Sp Novmentioning
confidence: 99%
“…Strains: 1, HG677 T (Sunxiuqinia rutila sp. nov.); 2, Sunxiuqinia elliptica DQHS4T (Qu et al, 2011;Takai et al, 2013); 3, Sunxiuqinia faeciviva JAM-BA0302…”
Section: Description Of Sunxiuqinia Rutila Sp Novmentioning
confidence: 99%
“…Although most of the members identified in this class are anaerobic, several aerobic and facultatively anaerobic strains have been reported recently. Sunxiuqinia faeciviva and Sunxiuqinia elliptica were isolated from deep sub-seafloor sediment and sediment in a sea cucumber farm, respectively (Qu et al, 2011;Takai et al, 2013), Prolixibacter bellariivorans was found in a marine-sediment fuel cell (Holmes et al, 2007), and Marinifilum fragile and Marinifilum flexuosum were recovered from tidal flat sediment and surface seawater, respectively (Na et al, 2009;Ruvira et al 2013). Recently, a novel family, 'Prolixibacteraceae' fam.…”
mentioning
confidence: 99%
“…Using a continuous downflow bioreactor system, phylogenetically diverse anaerobic microbes were successfully activated, including methanogens, such as the genera Methanobacterium, Methanoccoides, and Methanosarcina, and uncultured archaeal and bacterial lineages (Imachi et al, 2011). Several attempts at traditional batch-type cultivations have led to the isolation of novel anaerobic subseafloor microbes, including Geofilum rubicundum (Miyazaki et al, 2012) and Spinavirga faexivivus (Takai et al, 2013), which are the first representatives of previously uncultivated genera. These successful cultivations and isolations confirmed the presence of metabolically and/or physiologically active microbial populations in deep subseafloor sediments off the Shimokita Peninsula.…”
mentioning
confidence: 99%